Patient experience of advanced practice physiotherapy within low back pain care pathways in Canada and the United Kingdom: A multiple case-study protocol - Chris Davis; Katie Kowalski; Tim Noblet; Alison Rushton (PLoS ONE, 2026)
Introduction Low back pain (LBP) is the leading cause of disability worldwide, with high prevalence in Canada and the United Kingdom. LBP care pathways offer high-quality, guideline concordant care, with advanced practice physiotherapy (APP) an integral component. APP is a higher level of practice providing care for individuals with complex healthcare needs. Patient experience is an important measure of healthcare service quality. Although patient experience has been explored in some APP settings, and in standard physiotherapy for people with LBP, no study has explored patient experience of APP in LBP care pathways. Aim & Objectives To explore and understand how patients experience APP within low back pain care pathways in the UK and Canada. To map APP integration within LBP care pathways in the UK and Canada. To explore advanced practice physiotherapists’ perspectives on the patient experience of APP. To explore patients’ experience of APP. To synthesise the physiotherapists’ perspectives on the patient experience and patients’ experience of APP. To compare patient experience of APP between the UK and Canada. Methods A qualitative, exploratory, multiple case-study using an embedded (nested) design situated within a constructivist paradigm will be conducted. Cases will be LBP care pathways in Ontario, Canada and England, United Kingdom. AP physiotherapist and patient participants from both cases will be recruited through non-probability sampling. LBP care pathways will undergo framework analysis, quantitative questionnaire data will be reported descriptively, and interview and open text questionnaire data will undergo thematic analysis. Both within-case and cross-case analyses will be conducted. Significance This study may improve patient-centred care in LBP care pathways, inform APP educational programs and curricula design, address a knowledge gap in the APP literature, and inform future research by offering theoretical propositions relevant to patient experience of APP within LBP care pathways.